Analisis Pajak Penghasilan sebelum dan setelah Undang-Undang Nomor 7 Tahun 2021 bagi WP Orang Pribadi - Kurnianingsih, Retno (Journal Competency of Business, 2021)
Research on income tax is still an interesting topic considering that the regulation is very dynamic with several policy changes, as on October 7, 2021, the government issued Law Number 7 of 2021 (referred to as the HPP Law) concerning the Harmonization of Tax Regulations. There are 6 (six) scopes (clusters) of regulatory changes, namely: 1) General Provisions and Tax Procedures (KUP), Income Tax (PPh), Value Added Tax (PPN), Voluntary Disclosure Program (PPS) Carbon Tax and Excise. The largest source of revenue is from income taxes, therefore the government continues to strive to increase the target of state revenues by various means, both tax intensification and extensification, such as sunset policy, tax amnesty, tax imposition for MSMEs with PP No. 46/2013, renewed by providing tax incentives with PP No. 23/2018. However, it is felt that this implementation still does not provide justice for taxpayers, so the 2021 HPP Law is stipulated which will take effect from the 2022 tax year. This research is a qualitative descriptive study. The data analysis technique is by describing and analyzing based on existing theory and in accordance with the reality that occurs in the field by using calculation illustrations, namely comparing the old regulations with the PPh Law, PP No. 23/2018 and the HPP Law. Techniques for collecting data using library research, data obtained from secondary data by extracting information from various sources, seminar materials (webinar), mass media, electronic media, various books, documents and relevant writings to develop research concepts and supported by literature review. This study focuses on the income tax cluster for individual taxpayers. The purpose of this study is to analyze Income Tax before and after Law Number 7 of 2021 is enacted. Is the tax burden paid by taxpayers more profitable before or after the enactment of the HPP Law. Based on the results of the illustrative analysis of the calculation that for individual taxpayers (as employees) with income up to Rp. 60 million, the tax burden paid is lower under the HPP Law than the PPh Law because it is only exposed to the first layer of tariffs. Income >Rp60 million – Rp5 billion, the tax burden is lower under the HPP Law than the PPh Law. But income above IDR 5 billion, the tax paid is higher under the HPP Law than the PPh Law. Limitation on gross turnover of <Rp 500 million a year with a tax rate of 0%, then MSMEs that are subject to tax are those with gross turnover > Rp 500 million a year. So that the MSME tax burden is lower. The government's policy regarding taxes with various regulations that have issued "goals" is aimed at encouraging taxpayers to carry out bookkeeping and business development because of these regulations the validity period is valid and the end of its application when it has been completed returns to the general rate (Law No.36 of 2008) concerning income tax in conjunction with Law No. 7 of 2021. The existence of a progressive rate breaket gives a sense of tax justice, namely taxes are charged to taxpayers according to their ability to pay. The higher the income, the higher the tax imposed. The implication of further research is to analyze the regulation of changes in tax laws which are the main points in the HPP Law.